Assessment of early outcome in laparoscopic totally extraperitoneal inguinal hernia repair using lightweight mesh - Sivakumar, Sabhari Haran; Arora, Jainendra K.; Mandal, Nishith S. (International Surgery Journal, 2021)
Background: Laparoscopic surgery is dominating in the field of hernia. The search for the ideal prosthetic biomaterial has been a longstanding issue with debate over simple versus composite biomaterial and lightweight versus heavyweight meshes. This study was done to evaluate the early outcome of lightweight mesh in laparoscopic totally extraperitoneal (TEP) repair. Methods: This prospective observational study was done for a period of 16 months. On the basis of selection criteria patient underwent laparoscopic TEP repair using light weight mesh, early outcomes were evaluated in terms of immediate postoperative pain (analysed via visual analog scale) and chronic groin pain (analysed by visual analogue scale and graded according to Cunningham), patients were also evaluated for operation time, intraoperative bleeding, seroma, stiffness or numbness around groin, or any other complications. Results: There was no intraoperative bleeding among any of the patients. Immediate post-operative pain assessed by visual analogue scale 20% scored one in the visual analogue scale in post-operative day 1. None of the patients were having any complications (like stiffness or numbness in groin or thigh and any other complication) during post-surgery follow up. Only one patient reported mild chronic groin pain at the end of 3 months after surgery. Conclusions: The short term results of laparoscopic TEP repair for inguinal hernia using light weight mesh are quite encouraging. We can conclude that light weigh mesh is fulfilling important role in successful hernia repair as it is associated with very less morbidity.